Development and validation of the short form of the Parker personality measure among Chinese college students - Zhang, Yihua; Huang, Jing; Chen, Yangjie; Xu, Jiale; Meng, Runtang; Zhang, Bingren (Frontiers in Public Health, 2025)
ObjectiveCurrent diagnostic frameworks for pathological personality are shifting from categorical to dimensional models. While the Personality Inventory for DSM-5 represents the most extensively validated dimensional measure across Western and Eastern cultures, its length limits practical utility. This study developed the Parker Personality Measure Short Form (PERM-SF) to facilitate efficient screening of pathological personality traits.MethodsTwo samples of college students (Sample 1: N = 1,768; 937 women and 831 men, aged 20.59 years ± 1.95, ranging from 16 to 27 years; Sample 2: N = 1,614; 887 women and 727 men, aged 20.38 years ± 1.59, 17–27 years) were recruited consecutively from one university in China through online random sampling. Exploratory factor analysis in Sample 1 identified items with robust psychometric properties for inclusion in the PERM-SF. Confirmatory factor analysis in Sample 2 validated the factor structure. Subsequent analyses evaluated internal consistency, longitudinal measurement invariance, and construct validity.ResultsThirty-eight of the 92 items of PERM were deleted due to low factor loadings or high cross loadings, resulting in a five-factor model consisting of 54 items (F1: Dissociality, F2: Self-doubt-Detachment, F3: Disinhibition-Negative affectivity, F4: Anankastia, F5: Borderline pattern). All factors demonstrated good internal consistency (McDonald’s ω = 0.834–0.932). Longitudinal measurement invariance held at strict level (ΔCFI ≤ 0.001, ΔRMSEA ≤ 0.001) and two-way random-effects ICCs ranged from 0.488 to 0.759. Validity analyses revealed significant weak-to-moderate correlations with the Symptom Checklist-90 and established discriminant validity for all factor pairs, as supported by the Heterotrait-Monotrait Ratio test.ConclusionThe PERM-SF exhibits adequate preliminary psychometric properties for rapid assessment of pathological personality dimensions, supporting its utility for research and screening applications at least among Chinese young adults.